2020
DOI: 10.1111/aji.13234
|View full text |Cite
|
Sign up to set email alerts
|

SPRY4 regulates trophoblast proliferation and apoptosis via regulating IFN‐γ‐induced STAT1 expression and activation in recurrent miscarriage

Abstract: Problem:The dysregulation of trophoblast functions is one of the leading causes of recurrent miscarriage (RM), which frustrates 1%-5% of couples of childbearing ages. Sprouty 4 (SPRY4) is considered as a tumour suppressor and exerts a negative role in cell viability. However, its role in regulating trophoblast behaviors at the maternalfetal interface remains largely unknown. Method of Study:First-trimester villous samples were collected from RM patients and healthy controls (HCs) to determine the SPRY4 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…The establishment and maintenance of pregnancy poses great challenges to the maternal immune system. Uncoordinated maternal immunization, especially in the first trimester of pregnancy, will be a potential cause of a series of pregnancy complications (47,48). Currently, immunotherapy has been applied to the treatment of a variety of reproductive diseases, such as recurrent spontaneous abortion (RSA) and recurrent implantation failure (RIF) (49), while the immunotherapy against PIH still needs a long way to go.…”
Section: Discussionmentioning
confidence: 99%
“…The establishment and maintenance of pregnancy poses great challenges to the maternal immune system. Uncoordinated maternal immunization, especially in the first trimester of pregnancy, will be a potential cause of a series of pregnancy complications (47,48). Currently, immunotherapy has been applied to the treatment of a variety of reproductive diseases, such as recurrent spontaneous abortion (RSA) and recurrent implantation failure (RIF) (49), while the immunotherapy against PIH still needs a long way to go.…”
Section: Discussionmentioning
confidence: 99%
“…Following phosphorylation, STAT1 forms a homodimer and translocates to the nucleus where it binds to the conserved DNA sequence in the promoter region of the downstream target gene and activates its transcription (9). Previous studies have shown that IFN-γ could activate the JAK/STAT pathway in HTR-8/SVneo cells (41,42). STAT1 is phosphorylated at Ser727 and Tyr701 residues (43).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of ENO1 is also related to the progression of gliomas, and inhibiting ENO1 expression can inhibit the process of cell growth, migration and invasion by inactivating the PI3K/Akt pathway in glioma cells [16]. In previous studies on RM, cell proliferation, invasion, migration, and angiogenesis-related signaling pathways, such as the Wnt/β-catenin signaling pathway [17], the PI13K signaling pathway [18], and the ERK and other signaling pathways [19], participated in the occurrence and development of RM. Further research is needed to verify whether ENO1 affects the function of trophoblast cells through the above pathways.…”
Section: Discussionmentioning
confidence: 99%